Accounting Understanding and IT Utilization in Improving Financial Report Quality - Hari Setiyawati; Puji Rahayu; Dien Noviany Rahmatika; Dewi Indriasih (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
The urgency of this research is the importance of knowing the factors that can improve the quality of financial reports. This study aims to test the effect of accounting understanding and utilization of information technology on the quality of financial reports. The population of this study was cooperatives in the DKI Jakarta area totaling 3,447 cooperatives. The sampling method used was a purposive sampling technique with the criteria of cooperatives that had NIK (Cooperative Registration Number) certification and a sample of 97 cooperatives was obtained. Data were analyzed using the Structural Equation Model and Smart PLS software was used as an analysis tool in this study. The research data used came from questionnaires collected from administrators, managers, and financial staff of the cooperative. The results of this study indicate that accounting understanding has a significant positive effect on the quality of financial reports, while the utilization of information technology does not affect the quality of financial reports.